Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Kud Mina Fajar Sidik Blanakan Subang - Agit Riyadi; Enjang Suherman; Flora Patricia Anggela (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Work discipline can determine low or high performance, when employees do not obey rules such as time delays when working that are not inaccordance with applicable rules, it will hinder them from completing work on time before the specified deadline. This shows that there are still employee behaviors that are not in line with company expectations, such as employees who often arrive late and employees who are often absent without clear explanations. This study aims to identify, describe, analyze, and explain the relationship between work discipline and employee performance. This research was conducted using a descriptive verification method. The total population of the study was 70 respondents. The samples obtained by the saturated sampling method amounted to 70 respondents covering the entire population. Data analysis techniques using simple linear regression analysis, correlation coefficient test, partial t test, and r test of the coefficient of determination. Based on the results of the descriptive test, work discipline and employee performance are in good criteria. Based on the results of the verification test, work discipline has a positive and significant impact on employee performance with a strong correlation level and an influence contribution of 46.3%. Keywords : Work Discipline, and Employee Perfomance